2018
DOI: 10.1007/8904_2018_118
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the ABCD1 Protein with a Missense Mutation: A Novel Approach to Finding Therapeutic Compounds for X-Linked Adrenoleukodystrophy

Abstract: Mutations in the ABCD1 gene that encodes peroxisomal ABCD1 protein cause X-linked adrenoleukodystrophy (X-ALD), a rare neurodegenerative disorder. More than 70% of the patient fibroblasts with this missense mutation display either a lack or reduction of the ABCD1 protein because of posttranslational degradation. In this study, we analyzed the stability of the missense mutant ABCD1 proteins (p.A616T, p.R617H, and p.R660W) in X-ALD fibroblasts and found that the mutant ABCD1 protein p.A616T has the capacity to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…The human ABCD1 gene is found on chromosome Xq28 and contains ten exons. Mutations in ABCD1 cause X-linked adrenoleukodystrophy, a progressive neurodegenerative disease, characterized by the accumulation of very long chain fatty acids in plasma and tissues [ 107 ].…”
Section: Structure Function Expression and Gene Regulation Of Amentioning
confidence: 99%
“…The human ABCD1 gene is found on chromosome Xq28 and contains ten exons. Mutations in ABCD1 cause X-linked adrenoleukodystrophy, a progressive neurodegenerative disease, characterized by the accumulation of very long chain fatty acids in plasma and tissues [ 107 ].…”
Section: Structure Function Expression and Gene Regulation Of Amentioning
confidence: 99%
“…Here, Doa10p was suggested to play a major role in Pex15Δ30 degradation while Msp1p deals only with a fraction of Pex15Δ30 that is mistargeted to mitochondria. Because the authors followed the steady protein levels and not the rate of Pex15Δ30 turnover, it is plausible that in cells lacking Msp1p or Doa10p, Pex15Δ30 degradation is inhibited to a similar extent, suggesting that Msp1p and Doa10p act in the same pathway as proposed by (Matsumoto et al, 2019). Nevertheless, it is clear that Pex15Δ30 degradation is mediated by the ubiquitin proteasome system (UPS) which involves Msp1p, Doa10p and Cdc48p complex.…”
Section: Pex15pmentioning
confidence: 99%
“…Until now neither the mechanism of instability nor the proteases responsible for degradation of the mutant proteins have not been fully characterized. Recently, Takahashi et al, reported that the degradation of mutant ALDP protein was partially inhibited by treatment with MG132, suggesting that these ALDP mutants are degraded via the proteasome , Interestingly, a subset of unstable ALDP mutant proteins in patient cells became stable under low-temperature culture conditions and exhibited proper peroxisomal localization (Morita et al, 2019) while under these conditions patient cells displayed increased residual β-oxidation activity (Zhang et al, 2011). Some of the ALDP mutants which were rapidly degraded in vivo still possessed ATP hydrolysis activity in vitro , indicating that mutant forms of ALDP retain a certain degree of functionality.…”
Section: Aldpmentioning
confidence: 99%
See 2 more Smart Citations